Scoreless Draw Dance notation - McCarthy, Brendan (Dance Books Ltd., Alton,Hampshire (UK), 2008)
During a symposium at San Francisco Ballet's celebrations of its seventy-fifth anniversary there was a brief exchange about dance notation and its future.